تأثير الارتفاع عن سطح البحر على الخصائص الكيميائية للزيت العطري لنبات الزعتر البري النامي في مناطق متفرقة من الجبل الأخضر - حنان علي ادريس; عبدالسلام البخاري; أحمد جبريل محمد أبوبكر; عبدالمنعم فكرون; لمياء عبدالجليل; مريم الجنيد (Surman Journal of Science and Technology, 2021)
This study aimed to identify the effect of different altitudes above sea level on the chemical content of each of the essential oils and extracts of wild thyme, Thymus capitatus. Where the locations of Abu Dhra` and Sidi Al Hamri were selected, the plant samples were collected, the plant parts used in the study were dried, the volatile oil was extracted for each sample using the water distillation method, the crude extracts were prepared by following the successive extraction method, then the chromatographic separation method was carried out using thin-layer plates (TLC), and identification of the components of each volatile oil obtained from plants by GC/MS. The results of this study showed a quantitative and qualitative difference in the chemical content of the plant's essential oils as a result of the different study sites, the percentage of essential oil obtained from wild thyme from Abu Dra` and Sidi Al Hamri sites were (1.5%, 1.06%), respectively. The results of GC/MS showed the identification of 12 aromatic compounds with a percentage of (95.97%) of the total components of the essential oil of wild thyme from Abu Dhra’ site, and 20 aromatic compounds with a percentage of (87.53%) in wild thyme oil from Sidi Al-Hamri site, there are 7 common aromatic compounds in the study sites, which are Aromadendrene, Gamma-terpinene, Alpha-thujene, Thymol, Carvacrol, Delta-cadinene and Alpha-humulene. Berry (48.56%, 21.28%), respectively. The content of deoxygenated and oxygenated monoterpene hydrocarbons had the highest presence in the total content of the essential oil under study. The different extracts of the two plants under study were also prepared (extracts of hexane, chloroform and ethanol by successive extraction, and the total crude alcoholic extract was also prepared using the direct extraction method). The contents of these extracts were separated on silica gel plates by several separation systems and the number of separated packets in each feed was determined and RF values ​​were calculated for each bundle.